Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien di Puskesmas Batujajar - Neng Suyantiny; Angga Nadiyanto Prastian (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
Puskesmas Batujajar is one of 32 Puskesmas in West Bandung Regency whose purpose is to improve the quality of healthy life of the surrounding publics. This study aims to determine how much influence the quality service on patient satisfaction at the Batujajar Public Health Center. This study also uses a type of quantitative method through data collection techniques in the form of distributing questionnaires to 80 respondents. The questionnaire consists of 20 questions that represent each research variable. Each variable consists of Service Quality (X) and Patient Satisfaction (Y). Hypothesis testing using simple linear regression analysis and data processed using the SPSS program 29 version. The results of the study based on data processing through the SPSS version 29 application state that the value of tcount (12.031) > ttable (1,99085) with a significance value of 5%. So it can be concluded that the Service Quality variable has a significant effect on the Patient Satisfaction variable partially.